A Need for Updating the Research Agenda for Cleft Lip and Palate and Extending the Cleft Team Model to Dental Medicine - Vieira, Alexandre R. (Frontiers in Dental Medicine, 2021)
Care for individuals born with cleft lip and palate is done by a team approach, including dental medicine. However, oral health is not integrated in other situations that affect overall health. This perspective essay makes the case for a universal team approach, having dental medicine integrated regardless of the overall health issue, much like how cleft lip and palate is managed. Furthermore, future research agenda on the etiology of cleft lip and palate in particular will need to be adjusted for a major roadblock: the lack of more sophisticated clinical descriptions for the cases ascertained at birth.